Genetic characterization of the Indian cattle breeds, Ongole and Deoni (Bos indicus), using microsatellite markers – a preliminary study - Metta, Muralidhar (BioMed Central, 2004)
BACKGROUND: Molecular characterization of cattle breeds is important for the prevention of germplasm erosion by cross breeding. The Indian zebu cattle have their significant role in evolution of present day cattle breeds and development of some of the exotic breeds. Microsatellites are the best available molecular tools for characterization of cattle breeds. The present study was carried out to characterize two Indian cattle breeds, Ongole and Deoni, using microsatellite markers. RESULTS: Using 5 di- and 5 tri-nucleotide repeat loci, 17 Ongole and 13 Deoni unrelated individuals were studied. Of the ten loci, eight revealed polymorphism in both the breeds. The di-nucleotide repeat loci were found to be more polymorphic (100%) than tri-nucleotide repeat loci (60%). A total of 39 polymorphic alleles were obtained at 4.5 alleles per locus in Ongole and 4.1 in Deoni. The average expected heterozygosity was 0.46 (±0.1) and 0.50 (±0.1) in Ongole and Deoni breeds, respectively. The PIC values of the polymorphic loci ranged from 0.15 to 0.79 in Ongole and 0.13 to 0.80 in Deoni breeds. Six Ongole specific and three Deoni specific alleles were identified. The two breeds showed a moderate genetic relationship between themselves with a F(ST )value of 0.117 (P = 0.01). CONCLUSIONS: This preliminary study shows that microsatellite markers are useful in distinguishing the two zebu breeds namely, Ongole and Deoni. Further studies of other zebu breeds using many microsatellite loci with larger sample sizes can reveal the genetic relationships of Indian breeds.